Removal of lead, cadmium, and copper from wastewater using Cinnamon bark waste to introduce it as a value-added product: Removal, kinetics and thermodynamics study - Safaa Rasheed Yasin; Salwa Shamran Jasim; Israa Abdulwahab Al-Baldawi (Desalination and Water Treatment)
The results of heavy metals removal by Cinnamon bark waste were fruitful, as the removal efficiencies of the metals were 98.42, 93.04, and 88.80 %, and the uptake ratios were 12.30, 3.10, and 2.22 mg/g, using adsorbent dosages of 8, 30, and 40 g/L at time 1.5, 1.5, and 3 h for Pb2+ , Cd2+, and Cu2+, respectively. Adsorption conditions were a temperature of 30 ºC and a mixing speed of 100 rpm using an initial concentration of metals of 100 mg/L. While using an initial concentration of 10 mg/L, the adsorption efficiencies were 84.96, 95.85, and 93.37 % using adsorbent dosages of 8, 30, and 30 g/L for Pb2+, Cd2+, and Cu2+, respectively. The kinetics were Pseudo-second-order for the three ions. Isotherms were Langmuir for Pb2+, while they were Freundlich for Cd2+ and Cu2+. The mechanism of the adsorption was physisorption.